Static crushing material and static crushing method

JP2025034035APending Publication Date: 2025-03-13DENKA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023140164
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、鉄砲現象の発生が抑制され安全性の高い静的破砕材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034035000001_ABST
    Figure 2025034035000001_ABST
Patent Text Reader

Abstract

To provide a static crushing material with high safety that inhibits the occurrence of a flash flood phenomenon.SOLUTION: The static crushing material comprises a physically expansive material to be expanded by physical changes and a chemically expansive material to be expanded by chemical changes. Also provided is a static crushing method comprising: filling drilled holes of an object to be crushed with the static crushing material; and applying water to induce expansion.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a static crushing material and a static crushing method that are mainly used in the civil engineering and construction industries. [Background technology]

[0002] Conventionally, a so-called static crushing method is known for crushing brittle objects such as rocks or concrete without applying explosions or mechanical shocks. In the static crushing method, holes are made in the rocks or concrete in advance, and the holes are filled with an expansive slurry, which is then used to crush the rocks or concrete. For example, because quicklime has a large expansive force when hydrated, attempts have been made to use it as a crushing material.

[0003] However, quicklime alone has a very fast hydration rate, and when mixed with water, it immediately hydrates and expands, rapidly reducing its fluidity and making it difficult to inject into the holes. Even if it could be injected, it would blow out of the top of the hole due to a sudden exothermic reaction, a phenomenon known as gunfire, and sufficient crushing effects could not be achieved. It is not clear how the gunfire phenomenon occurs, but since the heat of hydration generated by the sudden exothermic reaction reaches about 120°C, it is assumed that a steam explosion is occurring.

[0004] As a static crushing material using quicklime, a method has been proposed in which a water-reducing agent is added to a mineral powder in which quicklime crystals are encapsulated in alite crystals, or a hydraulic substance and admixture are added to hard-burned quicklime powder, which is then mixed with water to form a paste, which is then injected into holes in rocks or concrete (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 55-142894 [Patent Document 2] Japanese Patent Application Publication No. 56-67059 Summary of the Invention [Problem to be solved by the invention]

[0006] However, although the methods described in Patent Document 1 and Patent Document 2 are material designs that appropriately control the hydration reaction of quicklime, there are limitations to the scope of application. In other words, the maximum drilled hole diameter is limited to less than 70 mm. If the drilled hole diameter exceeds 70 mm, the amount of static crushed material to be filled increases, so the amount of heat generated by hydration increases, increasing the risk of the gunshot phenomenon. Therefore, it was necessary to make the drilled hole diameter smaller than a certain size, narrow the drilling interval, and increase the number of drilled holes.

[0007] In addition, quicklime is produced by heating calcium carbonate (CaCO3) made from crushed limestone at high temperatures, which simultaneously produces carbon dioxide. Therefore, from the perspective of carbon neutrality, there will be a demand for static crushing materials that have a smaller environmental impact, such as reducing the amount of quicklime used.

[0008] In view of the above, an object of the present invention is to provide a static crushing material and a static crushing method which are highly safe and suppress the occurrence of gunshot phenomena. [Means for solving the problem]

[0009] The present inventors have conducted intensive research to achieve the above object, and have found that the above problems can be solved by the present invention described below. The present invention is based on the above findings and has the following gist.

[0010] [1] Static fracturing materials include physical change expanding materials that expand due to a physical change and chemical change expanding materials that expand due to a chemical change. [2] The static crushing material described in [1], in which the length of at least a portion of the physical change expansion material expands to 1.5 times or more 30 minutes after water is added. [3] The static crushing material according to [1] or [2], wherein the physical change expansion material is rod-shaped. [4] The static crushing material according to [3], wherein the diameter of the physical change expansion material is 30 mm to 100 mm. [5] The static crushing material according to any one of [1] to [3], wherein the physically changeable expansive material is compressed wood. [6] The static crushing material according to any one of [1] to [5], characterized in that the chemical change expansion material contains calcium oxide. [7] The static crushing material according to any one of [1] to [6], characterized in that the chemically reactive expansion material generates calcium hydroxide after chemical reaction. [8] The static crushing material according to any one of [1] to [7], characterized in that the chemically changed expansive material generates ettringite together with calcium hydroxide after chemical change. [9] A static crushing method in which the static crushing material according to any one of [1] to [8] is filled into a drilled hole in an object to be crushed and water is added to expand it.

[10] A static crushing method as described in [9], wherein the material to be crushed is a hardened cement body, boulders or bedrock. Effect of the Invention

[0011] According to the present invention, it is possible to provide a static crushing material which is highly safe and suppresses the occurrence of gunshots. [Brief description of the drawings]

[0012] [Figure 1] This is a schematic diagram showing an example of a combination of a physically changing expansion material and a chemically changing expansion material, where the upper side shows the top surface state and the lower side shows the axial direction state of the hole drilling. [Diagram 2] This is a schematic diagram showing another example of a combination of a physically changing expansion material and a chemically changing expansion material, where the upper side shows the top surface state and the lower side shows the axial direction state of the hole drilling. [Diagram 3] This is a schematic diagram showing another example of a combination of a physically changing expansion material and a chemically changing expansion material, where the upper side shows the top surface state and the lower side shows the axial direction state of the hole drilling. [Figure 4] This is a schematic diagram showing another example of a combination of a physically changing expansion material and a chemically changing expansion material, where the upper side shows the top surface state and the lower side shows the axial direction state of the hole drilling. [Diagram 5]Photographs showing the compressed wood of Experimental Example 1 before and after expansion, with the left side showing the wood before expansion and the right side showing the wood after expansion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the static crushing material and the static crushing method according to one embodiment of the present invention will be described in detail.

[0014] [Static crushing material] The static crushing material according to the present embodiment includes a physical change expanding material that expands due to a physical change and a chemical change expanding material that expands due to a chemical change. Physically changing expansive materials do not undergo a chemical change in their own material and expand as a result of this, but rather expand by causing a volume change when water is added, without changing the material itself. Therefore, physically changing expansive materials do not generate intense heat or cause gunfire, making them very safe to handle. Furthermore, if compressed wood, which will be described later, is used as the physical change expanding material, the manufacturing process does not emit carbon dioxide, so the environmental load can be reduced.

[0015] A chemically reactive expanding material undergoes a chemical change in its own material, which causes it to expand. A representative example is an expanding material mainly made of calcium oxide, which will be described later. This utilizes the volume expansion that occurs when calcium oxide undergoes a chemical reaction with water and changes into calcium hydroxide. If only this chemically reactive expanding material is used, there is a risk of intense heat generation and gunfire, but in the present invention, by combining it with a physically reactive expanding material, the risk of gunfire can be reduced or eliminated, and the crushing effect can be improved. Specifically, the time required for crushing can be shortened.

[0016] It is preferable that at least a portion of the length of the physical change expansion material expands to 1.5 times or more 30 minutes after water is applied. If the length expands to 1.5 times or more 30 minutes after water is applied, a good crushing effect is easily obtained. The expansion after water is applied is preferably 1.8 times or more, and more preferably 2.0 times or more. The upper limit is not particularly limited, but in practice it is about 2.5 times.

[0017] The expansion (expansion rate) of a physical change expansion material can be determined by submerging the material in a container filled with pure water at 20°C, removing it after 30 minutes, measuring the length of the most expanded part (B), and calculating "B / A" from the length (A) of the part before expansion that corresponds to the most expanded part. When measuring the expansion coefficient, the expansion coefficient of the physical change expansive material is measured in an unconstrained state. The physical change expansive material is in the form of a round bar having a diameter of 30 to 100 mm.

[0018] For example, when the physical change expansion material is in the shape of a round rod, the diameter before expansion corresponds to the above "A", and the maximum length after expansion (the long axis length perpendicular to the axial direction) corresponds to the above "B". The expansion rate can be adjusted, for example, by adjusting the compression rate when densified wood is produced using densified wood as an expanding material.

[0019] Examples of physical change expanding materials include densified wood, water swelling rubber, water absorbing polymers, plant-derived expanding materials such as "growing wakame" (seaweed) and loofah, and clay minerals such as bentonite. Densified wood is preferred from the viewpoint of reducing the environmental load and from the viewpoint of crushing performance. Densified wood is a material with a small CO2 emission unit and a small environmental load. In addition, since it can be made from domestic wood, it can contribute to the spread of domestic wood and the reduction of CO2.

[0020] Densified wood has a density of, for example, 0.5 to 1.1 g / cm 3 Specifically, the wood is made of compressed wood that has been compressed to the above density. This compressed wood is wood that has been compressed by compressing it with a press or the like.

[0021] The density of physical change expansive materials (especially compressed wood) is 0.5 to 1.1 g / cm 3 It is preferable that the density is 0.5 to 1.1 g / cm 3 This allows for good crushing performance and weight reduction. The density is 0.75 to 1.05 g / cm 3 and preferably 0.8 to 1.0 g / cm 3 It is more preferable that: The density can be measured and determined in accordance with JIS Z 2101 (testing method for wood).

[0022] The physical change expansion material according to the present embodiment is preferably a rod-shaped bar material. When the bar material is a round bar, the diameter is preferably in the range of 30 mm to 100 mm, more preferably in the range of 40 mm to 80 mm. By being 30 mm or more, sufficient crushing force is easily obtained, and by being 100 mm or less, the crushing force is improved while the productivity of the physical change expansion material is also improved, and a balance between these can be achieved. When the rod material has a shape other than a round bar, it is preferable that the circle-equivalent diameter of the cross section perpendicular to the longitudinal direction is within the above range.

[0023] The chemically reactive expansive material according to this embodiment is, for example, a material that reacts with water to chemically react into a hydrate, and expands in volume during this process. Specific examples of the material include those that contain calcium oxide, such as those that are mainly composed of calcium oxide, and those that contain calcium oxide together with calcium aluminates and gypsums, and contain a component that generates ettringite (3CaO·Al2O3·3CaSO4·32H2O) through hydration. In other words, the chemical reaction expansive material is preferably one that generates calcium hydroxide after chemical reaction, such as calcium oxide, or one that generates ettringite together with calcium hydroxide after chemical reaction. These have the characteristic of having a large expansion energy per unit volume of the chemical reaction expansive material, so by using them well within the allowable range of heat generation, efficient crushing force can be obtained.

[0024] Those mainly made of calcium oxide may contain calcium silicate (3CaO·SiO2 or 2CaO·SiO2) or gypsum for the purpose of controlling the hydration rate. In the case of this calcium oxide-based chemical reaction expansive material, the calcium oxide content is preferably 50% by mass or more, and more preferably 60% by mass or more. By having a content of 50% by mass or more, it becomes easier to obtain good expansive properties of calcium oxide.

[0025] In the case of an ettringite-forming chemical reaction expansive material in which calcium aluminates and gypsums are present together with calcium oxide, the content of calcium aluminates is preferably 5 to 30 mass%, more preferably 10 to 20 mass%. The content of gypsums is preferably 10 to 45 mass%, more preferably 20 to 30 mass%. With the above content range, good expansiveness is easily obtained.

[0026] The calcium aluminates are a general term for compounds mainly composed of CaO and Al2O3. Specific examples include CaO·2Al2O3, CaO·Al2O3, 12CaO·7Al2O3, 11CaO·7Al2O3·CaF2, 3CaO·Al2O3, 3CaO·3Al2O3·CaSO4, and amorphous substances mainly composed of CaO and Al2O3.

[0027] The method for industrially producing these calcium aluminates is not particularly limited, but examples of the CaO raw material include calcium carbonate such as limestone or shells, calcium hydroxide such as slaked lime, or calcium oxide such as quicklime, and examples of the Al2O3 raw material include bauxite, aluminum dross, and aluminum ash residue, etc. Examples of the method include mixing these CaO raw materials and Al2O3 raw materials and heat treating them at a high temperature of 1,000°C or more.

[0028] When these calcium aluminates are obtained industrially, they may contain impurities, specific examples of which include SiO2, Fe2O3, MgO, TiO2, MnO, Na2O, K2O, Li2O, S, PO, and B2O3.

[0029] Gypsum is a general term for anhydrous gypsum, hemihydrate gypsum, and dihydrate gypsum, and any type can be used.

[0030] The chemical reaction expansion agent can be used in powder or granular form. It is also possible to use the powdered or granular chemical reaction expansion agent in a capsule-like form by wrapping it in a water-absorbing packaging material such as Japanese paper. When used in powder form, the fineness of the chemical reaction expansion agent is 1500 to 5000 cm in terms of Blaine specific surface area. 2 / g, and 2000 to 4000 cm 2 / g. The Blaine specific surface area is preferably 1500 to 5000 cm 2 / g, it is possible to improve the adhesion with the physical change expansive material and the filling property into the drilled hole. The Blaine specific surface area can be measured in accordance with JIS R 5201 (physical test method for cement).

[0031] When used in granular form, the particle size of the chemical reaction expansion material may be in the range of 1 to 5 mm. In addition, when using the chemical reaction expansion material in powder form, it is preferable to use a retarder or water-reducing agent in combination. Static crushing materials using commercially available chemical reaction expansion materials are industrialized with appropriate blends of water-reducing agents and retarders, and these commercially available products can be used.

[0032] Static crushing materials mainly made of chemical reaction expansive materials are already commercially available, and specific examples include "Blister" manufactured by Pacific Materials Co., Ltd., "S-Mite" manufactured by Sumitomo Osaka Cement Co., Ltd., and "Splitter" manufactured by Yoshizawa Lime Industry Co., Ltd. In addition, concrete expansive materials can also be used as chemical reaction expansive materials, and specific examples include "Expan" and "HyperExpan" manufactured by Pacific Materials Co., Ltd., and "Power CSA" manufactured by Denka Co., Ltd.

[0033] The static crushing material according to this embodiment uses a combination of a physical change expansion material and a chemical change expansion material, and although the ratio is not particularly limited, it is preferable that the physical change expansion material is 50 to 90 volume %, and more preferably 60 to 80 volume %. By including 50 volume % or more of the physical change expansion material, the bullet phenomenon can be suppressed. By making the physical change expansion material 90 volume % or less (by making the chemical change expansion material 10 volume % or more), the crushing effect can be stabilized. In this embodiment, in addition to the physical change expansion material and the chemical change expansion material, for example, fillers such as wood chips, Japanese paper or cloth, sand or gravel, limestone fine powder or silica fine powder can be included. In this case, the total of the physical change expansion material and the chemical change expansion material in the static crushing material is preferably 50 volume % or more, and more preferably 75 volume % or more from the viewpoint of good expansion properties.

[0034] In this embodiment, the method of combining the physical change expansion material and the chemical change expansion material is not particularly limited, but specific examples are shown in Figs.

[0035] Figure 1 is a schematic diagram of a physical change expansion material made of compressed wood 10, cut into a cylindrical rod (round bar), inserted into a hole 14 in a material to be crushed 12 such as concrete, rock, or boulders, and filled with chemical change expansion material 16 around it.

[0036] Figure 2 is a schematic diagram showing how, like Figure 1, compressed wood 10 is used as a physical change expansion material, which is cut into cylindrical rods, but the rods are shortened in length and divided, and inserted alternately with chemical change expansion material 16 into drilled holes 14 in the material to be crushed 12. Figure 3 is a schematic diagram showing the use of compressed wood 10 as a physical change expansion material, which is turned into wood chips and mixed with a chemical change expansion material 16, then wrapped in a packaging material 18 such as Japanese paper to form an encapsulated form, and then inserted into a drilled hole 14 in the material to be crushed 12. Fig. 4 is a schematic diagram of a case where, like Fig. 1, densified wood 10 is used as a physical change expansive material, which is made into a rod, processed into a hollow tube, and inserted into a drilled hole 14 in an object to be crushed 12, and then the hollow part of the densified wood 10 is filled with a chemical change expansive material 16. If there is a space outside the densified wood 10, the space may be further filled with a chemical change expansive material 16.

[0037] [Method of manufacturing statically crushed material] A method for producing the statically crushed material according to this embodiment in which the physical change expansive material is compressed wood will be described below.

[0038] (Production of compressed lumber) Densified wood is (1) A drying process in which the raw wood is dried at 40 to 100°C to produce dried wood; (2) It is preferable that the wood be produced through a compression process in which the dried wood is subjected to a pressure compression treatment of 2 to 5 MPa in the thickness direction to form compressed wood. Each step will be described below.

[0039] (1) Drying process In the drying process, raw wood of a predetermined size is dried at 40 to 100°C to obtain dried wood. In the drying process, the raw wood is placed in a dryer set at a drying temperature of about 40 to 100°C and a wet-dry bulb temperature difference of about 1 to 30°C so that the moisture content is 10% by mass or less on average, and dried to obtain dried wood. The dried wood may be further subjected to a firing process at a high temperature of about 300°C for a short period of time. These drying and firing processes can be performed using a steam dryer, a hot water dryer, a pressure dryer, an electric dryer, or the like.

[0040] There is no particular limit to the type of raw wood, and any wood can be used. Specific examples include domestic coniferous trees such as red pine, black pine, yew, ginkgo, Japanese yew, Japanese spruce, Japanese kaya, larch, Japanese cedar, sawara, Japanese cedar, hemlock, Japanese dormosum, Japanese larches, Japanese cypress, Japanese cypress, cypress, Japanese cedar, Himekomatsu, and fir.

[0041] Domestic broad-leaved trees include blue ash, Japanese ash, red oak, asada, racemosum, silver maple, Chinese laurel, Japanese snowbell, Japanese walnut, persimmon, katsura, phellodendron amplexicaule, paulownia, camphor tree, chestnut, zelkova, Japanese laurel, cherry, Japanese walnut, hornbeam, linden, white oak, white birch, Machilus, boxwood, horse chestnut, poplar, false acacia, Japanese elm, Japanese alder, beech, magnolia, makamba, dogwood, Japanese oak, beech, Japanese bead tree, Japanese bead, Japanese ash, willow, and Japanese mulberry.

[0042] Examples of foreign conifers include agathis, Scots pine, Caribbean pine, Crinkle pine, southern yellow pine, spruce, Japanese cypress, Western cedar, Western hemlock, Japanese cypress, Japanese hiba, Douglas fir, Japanese fir, red pine, Japanese red pine, Honsun pine, and others, Japanese larch, ponderosa pine, radiata pine, Mexican cypress, redwood, and lodgepole pine.

[0043] Foreign hardwoods include Acacia mangium, Azobé, Apitong, African mahogany, Albizia, Yellow birch, Yellow poplar, Yellow meranti, Ipe, Iroko, Erima, Okoume, Obeche, Alder, Kapoor, Kapok, Camelele, Quince, Calophyllum, Gubas, Gelongan, Kempas, Cordia, Ebony, Kokrojua, Coconut, Rubber tree, Sapele, Jelutong, Jara, Jongkong, Silver beech, Spanish cedar, Scepter, Soft maples, Dark red maples, Some of the woods that can be used include Red Meranti, Taung, Dao, Tagayasan, Teak, Nato, Hard Maple, Basswood, Balsa, Beech, Hickory, Bubinga, Ply, Black Walnut, Black Cherry, Black Bean, Perpok, White Ash, White Oak, White Meranti, Makore, Mahogany, Maras, Mansonia, Melina, Mersawa, Merbau, Mengelis, Monkey Pot, Light Red Meranti, Labra, Ramin, Lignum Vita, Red Oak, and Rosewood.

[0044] The raw wood material is not particularly limited, but from the viewpoint of effective use of natural resources, thinned wood can be used, and a representative example is cedar.

[0045] (2) Compression process In the heat compression step, the dried wood is compressed by applying a pressure of 2 to 5 MPa in the thickness direction to produce compressed wood. The temperature at this time is preferably 80°C to 200°C, which is the softening temperature of wood.

[0046] The process of heating and compressing dried wood preferably involves raising the upper press platen relative to the lower press platen on the fixed side of the press platens, placing the dried wood in the compression space formed by the upper and lower press platens, lowering the upper press platen relative to the lower press platen at a pressure of 0.05 to 0.30 MPa so as to abut against the grain surface side of the dried wood, setting the compression pressure of the upper press platen relative to the fixed side of the lower press platen to 2.0 to 5.0 MPa, and compressing the dried wood with the upper and lower press platens at a compression speed of 15 to 100 mm / min for a treatment time of 10 to 40 minutes. The compression ratio in the compression process (thickness after compression / thickness before compression×100) is not particularly limited, but is preferably in the range of 30% to 60%.

[0047] The obtained compressed wood is preferably processed so that it can be inserted into holes drilled in concrete, boulders, or bedrock. Specific examples of this include processing the wood into rods or forming the wood into a sawdust-like shape. Rods are preferred from the viewpoint of obtaining a high crushing effect. The rods may have a cross-sectional shape that is circular, polygonal (triangle, square, pentagon, hexagon, etc.), or even star-shaped. The densified wood may be made of one material or multiple materials. For example, if the diameter of the drilled hole is large, the diameter of the densified wood must be large. In this case, two or three pieces of densified wood can be glued together in the axial direction with an adhesive to produce densified wood of the desired diameter.

[0048] [Static crushing method] The static crushing method according to this embodiment is a method in which the static crushing material is filled into a drilled hole in the object to be crushed and expanded by adding water. The object to be crushed is preferably a cement hardened body, boulders, or bedrock. The cement hardened body may be a cement base hardened body, a mortar hardened body, or a concrete hardened body.

[0049] Here, when the physical change expansion material in the static crushing material is rod-shaped, it is preferable that the diameter of the hole drilled in the hardened cement body, boulder, or bedrock and the diameter of the physical change expansion material satisfy the following formula (1). Formula (1): Diameter of hole drilled in concrete, boulder, or rock > Diameter of physical change expansive material

[0050] Here, the difference between the diameter of the hole drilled in the concrete, boulder, or bedrock and the diameter of the physical change expansion material can be expressed as a clearance, and the clearance is expressed by the following formula (2). Formula (2): Clearance = diameter of hole drilled in concrete, boulder, or rock - diameter of physical change expansive material

[0051] In this embodiment, the clearance is not uniquely determined by the size of the drilled hole diameter, but is preferably 10 mm or less, more preferably 5 mm or less. The clearance serves to promote the supply of water to the physical change expansive material and also serves as a filling space for the chemical change expansive material, but if the clearance is 10 mm or less, the proportion of the chemical change expansive material used decreases and heat generation decreases.

[0052] In the static crushing method, it is preferable to carry out secondary crushing after primary crushing using a static crushing material (agent). Secondary crushing is the work of dismantling concrete, boulders, and rocks that have been cracked by primary crushing. A breaker is generally used as the secondary crusher, but a nibbler or ripper may also be used. In the static crushing method using conventional quicklime-based static crushing materials, that is, static crushing materials that rely only on chemical change expansion materials, secondary crushing work could not be carried out until 10 hours after the static crushing material was injected. This is because the gun phenomenon may occur only after the hydration reaction of the quicklime-based static crushing material has completely finished and the heat of hydration has subsided, and sufficient time is required from a safety perspective. Therefore, in the static crushing method using conventional quicklime-based static crushing materials, secondary crushing work was generally carried out the next day.

[0053] In addition, in the method using a static crushing material based on quicklime, that is, a static crushing material that relies only on a chemical reaction expansion material, the hydration reactivity of quicklime decreases especially at low temperatures below 10°C, and crushing can take 2 to 3 days, and at temperatures below 5°C, crushing can take more than a week. Conversely, in high temperature environments above 30°C, the gunshot phenomenon can occur. Furthermore, in this static crushing method, cracks are introduced by the primary crushing using the static crushing material, and then the building is demolished by secondary crushing. However, in order to work safely and avoid the risk of gunshot phenomenon, the work standard requires that the secondary crushing work be performed at an interval of 10 hours or more after the injection of the static crushing material. Therefore, secondary crushing was generally performed the day after the primary crushing.

[0054] In contrast, the static crushing material according to the present embodiment can significantly reduce the heat generated by hydration, realizing a safe static crushing method, and secondary crushing can be performed immediately after the completion of primary crushing, making it possible to complete the process from primary crushing to secondary crushing in one day. In other words, the static crushing method according to the present embodiment can perform the crushing process safely and efficiently because the work is not temperature-dependent.

[0055] The static crushing material described above is used, for example, to crush rocks, boulders, and unnecessary concrete structures. Note that "boulders" refer to rock masses on the surface or underground, such as rocks that have broken off from outcrops and are scattered onto mountainsides or rivers. Therefore, depending on where the rocks fall, heavy machinery cannot reach them and removal work becomes difficult when they fall on slopes or the ground due to natural disasters such as earthquakes and volcanic eruptions. If the fallen rocks are left unattended, there is a risk of secondary disasters. In such cases, a static crushing material that can be safely used in places where crossing work is required during disasters and emergency response, or where multiple people are moving and crossing, is required, and the static crushing material of the present invention can be used optimally in such cases. EXAMPLES

[0056] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0057] [Experimental Example 1] <Experiments No. 1, 3, 5> (Physical change: Production of expansive materials) The raw wood material, cedar boards (100 mm x 300 mm, 110 mm thick), was dried at 80°C using a pressure wood dryer to produce dried wood. The dried wood was compressed in the thickness direction by a compressor at a pressure of 5 MPa (temperature: about 90°C) to produce compressed wood (100 mm x 300 mm, thickness: 55 mm, density: 0.8 g / cm 3 A round bar with a diameter of 50 mm and a length of 300 mm was cut out perpendicular to the thickness direction from the side of this compressed wood, and then cut to a length of 100 mm.

[0058] (Measurement of the expansion rate of physical change expansion materials) Cut compressed wood is submerged in a container of pure water at 20°C, then removed after 30 minutes and the length of the most expanded part (B) is measured. This can be calculated by dividing the length (B) by the length of the part before expansion that corresponds to the most expanded part (A). Photographs of compressed wood before and after expansion are shown in Figure 5. As shown in Figure 5, A is the diameter (50 mm) and B is the long axis length of the ellipse.

[0059] (Evaluation of crushing time, etc.) Five holes, each 55 mm in diameter and 570 mm deep, were drilled in a 600 x 600 x 600 mm unreinforced concrete body. The distance between the holes was 100 mm. After filling these holes with water, five of the prepared physical change expansive materials were immediately inserted after wetting them with water, and chemical change expansive material A was mixed with water to form a paste and injected into the clearance (5 mm). The primary crushing time was measured at 5°C, 20°C, and 30°C. In addition to the temperature inside the drilled hole to estimate the risk of gunfire, the magnitude of the environmental load caused by the static crushing material was also evaluated. The results are shown in Table 1. The temperature inside the drilled hole was measured by placing thermocouples at three points (top, middle and bottom) along the depth of the inner concrete wall inside the drilled hole, and the average value was calculated. (Materials used) Chemical change expansion material A: quicklime-based static crushing material, "Blister" manufactured by Pacific Materials Co., Ltd., powder form, Blaine specific surface area 2200 cm 2 / g.

[0060] The assessment of the environmental impact was considered from the perspective of CO2 emissions during the manufacture of static crushing materials, and the magnitude of CO2 emissions derived from raw materials and energy was considered. Conventional quicklime-based static crushing materials are obtained by burning the raw material limestone (calcium carbonate) at high temperatures in a furnace, so there are large emissions of both raw material-derived CO2 and energy-derived CO2. Therefore, reducing the amount of chemical reaction expansive material used leads to a reduction in the environmental impact. Here, the relationship between the volume of the physical reaction expansive material and the volume of the chemical reaction expansive material is expressed by the following formula (3).

[0061] Formula (3): Volume of drilled hole - Volume of physical change expansive material = Volume of chemical change expansive material The volume of the chemical reaction expansion material actually filled in the drilled hole was defined as 100% when the volume of the chemical reaction expansion material was filled entirely inside the drilled hole, and the volume ratio of the chemical reaction expansion material actually filled in was defined as the relative volume value and evaluated.

[0062] <Experiments No. 2, 4, 6> Instead of using compressed wood as the static crushing material, a quicklime-based static crushing material (manufactured by Pacific Materials, product name: Blaster) was used, and the five holes were filled with the quicklime-based static crushing material and sufficient water was added, but the primary crushing time was measured in the same manner as in Experiments Nos. 1, 3, and 5. The magnitude of the environmental load caused by the quicklime-based static crushing material was also evaluated. The results are shown in Table 1.

[0063] [Table 1]

[0064] It can be seen that the static crushing material of this embodiment has a smaller risk of the occurrence of the gunshot phenomenon, is less temperature-dependent, and has a smaller environmental impact than the conventional quicklime-based static crushing material.

[0065] [Experimental Example 2] In experiment No. 1, compressed wood was produced by changing the pressure (compression rate) of the pressurization process when producing compressed wood so that the expansion rate would be the ratio shown in Table 2, and the crushing time, etc. were evaluated. The results are shown in Table 2. The temperature for the primary crushing was 20°C.

[0066] [Table 2]

[0067] As shown in Table 2, an expansion rate of 1.5 times or more enabled the crushing time to be particularly shortened.

[0068] [Experimental Example 3] (Evaluation of diameter and hole spacing of statically crushed material) The same experiment was carried out using a 600 x 600 x 600 mm unreinforced concrete hardened body, except that the diameter of the physical expansion material, the number of drilled holes, and the distance between holes were changed as shown in Table 3. The results are shown in Table 3. In all cases, the drilled hole diameter was the diameter of the physical expansion material + 5 mm.

[0069] [Table 3]

[0070] From Table 3, we can see that by increasing the diameter of the static crushing material, the number of holes to be drilled can be reduced and the distance between holes can be increased. This makes the crushing work more efficient. In addition, the larger the drilling diameter, the smaller the amount of chemical reaction expansion material, which has a large environmental impact, that is used.

[0071] [Experimental Example 4] (Evaluation of types of chemically modified expansive materials) The same experiment was carried out using a 600 x 600 x 600 mm unreinforced concrete hardened body, with the diameter of the physical change expansive material set to 50 mm, the number of holes drilled set to 5, the distance between holes set to 10 cm, and the type of chemical change expansive material changed as shown in Table 4. The results are shown in Table 4. In all cases, the diameter of the holes drilled was set to the diameter of the physical expansive material + 5 mm. (Materials used) Chemically modified expansive material B: Ettringite-lime composite concrete expansive material, Denka Power CSA manufactured by Denka Co., Ltd., powder form, Blaine specific surface area 3000 cm 2 / g. Contains 50% free lime, 25% anhydrite, and other hydraulic compounds.

[0072] [Table 4]

[0073] From Table 4, it can be seen that ettringite-lime composite type expansive agent for concrete (ettringite-forming type chemical change expansive agent) is also applicable. [Industrial Applicability]

[0074] INDUSTRIAL APPLICABILITY The present invention can be used for static crushing materials mainly used in the civil engineering and construction industries, in particular for static crushing methods for crushing brittle objects such as rocks or concrete without applying explosions or mechanical shocks. [Explanation of symbols]

[0075] 10. Densified Wood 12 Crushed material 14 Drilling 16 Chemically-Reacting Expansive Materials 18 Packaging materials

Claims

1. A static crushing material including a physical change expanding material that expands due to a physical change and a chemical change expanding material that expands due to a chemical change.

2. The static crushing material according to claim 1, wherein the length of at least a part of the physically changing expansion material expands to 1.5 times or more 30 minutes after water is applied thereto.

3. The static crushing material according to claim 1 or 2, wherein the physical change expansion material is rod-shaped.

4. The static crushing material according to claim 3, wherein the diameter of the physical change expansion material is 30 mm to 100 mm.

5. The static crushing material according to claim 1 or 2, wherein the physically changing expansive material is compressed wood.

6. 2. The static crushing material according to claim 1, wherein the chemically reactive expansion material comprises calcium oxide.

7. The static crushing material according to claim 1 or 6, characterized in that the chemically changed expanding material generates calcium hydroxide after chemical change.

8. The static crushing material according to claim 1, characterized in that the chemically changed expansive material generates ettringite together with calcium hydroxide after chemical change.

9. A static crushing method comprising filling the static crushing material according to claim 1 or 6 into a drilled hole in an object to be crushed and adding water to cause it to expand.

10. 10. The static crushing method according to claim 9, wherein the object to be crushed is a hardened cement body, a boulder, or a rock face.

Citation Information

Patent Citations

  • Agent for breaking brittle piece

    JP1980142894A

  • Destroying agent for brittle matter

    JP1981067059A